2021
DOI: 10.1177/20406223211058332
|View full text |Cite
|
Sign up to set email alerts
|

Skin barrier status during dupilumab treatment in patients with severe atopic dermatitis

Abstract: Background: Atopic dermatitis (AD) is a common chronic-relapsing inflammatory skin disease hallmarked by epidermal barrier dysfunction, increased transepidermal water loss (TEWL) and decreased skin hydration. Recent findings on the T helper 2 (Th2)-driven pathogenesis of AD have led to the development of dupilumab, a monoclonal antibody directed against interleukin-4 and interleukin-13 that has been demonstrated to be effective in the treatment of moderate-to-severe AD. The effect of dupilumab on skin barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The dose of dupilumab used in five of them was the one recommended in the datasheet (a subcutaneous injection of dupilumab 300 mg every other week following a loading dose of 600 mg Dupilumab dose). Only Berdyshev et al used a different dose in patients with weight below 60 kg: a loading dose of 400 mg with subsequent doses of 200 mg. Two researches did not include any comparison group 16,17 and three articles included healthy individuals as the comparison group 15,18,19 . Only one study compared the impact of dupilumab on skin barrier function with other treatments, including topical corticosteroids and cyclosporine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of dupilumab used in five of them was the one recommended in the datasheet (a subcutaneous injection of dupilumab 300 mg every other week following a loading dose of 600 mg Dupilumab dose). Only Berdyshev et al used a different dose in patients with weight below 60 kg: a loading dose of 400 mg with subsequent doses of 200 mg. Two researches did not include any comparison group 16,17 and three articles included healthy individuals as the comparison group 15,18,19 . Only one study compared the impact of dupilumab on skin barrier function with other treatments, including topical corticosteroids and cyclosporine.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with AD have high TEWL values reflecting skin barrier dysfunction. It is important to restore skin barrier and decrease local and systemic inflammation for a successful management of AD 17 . Ceramide emollients and topical treatments, including corticosteroids and calcineurin inhibitors, decrease TEWL improving skin barrier in patients with AD 30–32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies have also evaluated the impact of dupilumab on skin barrier function [ 46 , 47 , 48 , 49 , 50 ]. They showed that dupilumab reduced TEWL on non-involved and involved skin [ 46 , 47 , 48 , 49 , 50 ]. The impact of dupilumab in SCH differs between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal barrier dysfunctions in the lesional and nonlesional skin of patients is a critical feature of AD; these dysfunctions result in a greater transepidermal water loss (TEWL) and also a decrease in skin hydration [ 110 , 111 ].…”
Section: Skin Aquaporins In Inflammatory Dermatological Diseasesmentioning
confidence: 99%